UV radiation below an Arctic vortex with severe ozone depletion - Knudsen, B. M.; Jønch-Sørensen, H.; Eriksen, P.; Johnsen, B. J.; Bodeker, G. E. (HAL CCSD, 2005)
International audience The erythemally weighted (UV) irradiance below the severely depleted Arctic vortices in spring 1996 and 1997 were substantially elevated. On average the UV increased 36 and 33% relative to the 1979-1981 mean assuming clear skies from day 80-100 in 1996 and 1997, respectively. On clear sky days large regions of the Arctic experienced maximum UV increases exceeding 70 and 50% on single days in 1996 and 1997, respectively. A minor fraction of these increases are not anthropogenic and have a dynamical origin as seen by comparison to 1982, when hardly any ozone depletion is expected.